Back home to Mauritius! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
After no less than seventeen years of service with CTA Mohun Narain, who in recent years has led CTA's Information Policies and Partnerships Department, is set to enjoy his retirement on his island home of Mauritius. Mohun, who studied agriculture...